2020
DOI: 10.1039/d0sc04100a
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-protected gold/silver superatoms: current status and emerging trends

Abstract: Monolayer-protected gold/silver clusters have attracted much interest as nano-scale building units for novel functional materials owing to their nonbulk-like structures and size-specific properties. They can be viewed as ligand-protected superatoms...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
81
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(83 citation statements)
references
References 159 publications
2
81
0
Order By: Relevance
“…Atomically precise metal nanoclusters have gained extensive interests due to intriguing their graceful structures and fascinating chemical/physical properties. [189][190][191][192][193][194][195][196][197][198][199][200][201][202] Meanwhile, one of the most charming and significant properties of metal clusters is luminescence, whereas it remains a challenge that obtaining metal clusters with bright luminescence at room temperature due to the instability and their sensitivity to the external environment. [191,203,204] Thus, aiming to the difficulty, some strategies that thermally assisted delayed fluorescence (TADF), AIE as well as crystallization-emission (CIE) have been proposed and validated.…”
Section: Metal Clusters and Cluster-based Materialsmentioning
confidence: 99%
“…Atomically precise metal nanoclusters have gained extensive interests due to intriguing their graceful structures and fascinating chemical/physical properties. [189][190][191][192][193][194][195][196][197][198][199][200][201][202] Meanwhile, one of the most charming and significant properties of metal clusters is luminescence, whereas it remains a challenge that obtaining metal clusters with bright luminescence at room temperature due to the instability and their sensitivity to the external environment. [191,203,204] Thus, aiming to the difficulty, some strategies that thermally assisted delayed fluorescence (TADF), AIE as well as crystallization-emission (CIE) have been proposed and validated.…”
Section: Metal Clusters and Cluster-based Materialsmentioning
confidence: 99%
“…Various strategies, such as heteroatom doping ( Wang et al, 2014 ), aggregation-induced-emission (AIE) ( Luo et al, 2012 ), and assembly induced emission enhancement ( Wu et al, 2019a ), have been developed to prepare highly luminescent Au and Ag NCs. Since the crystal structure of ligand-protected Au NCs, which are usually comprised of metallic core and peripheral gold(I)-thiolate staple motifs, have been revealed at atomic resolution ( Jadzinsky et al, 2007 ), heteroatom substitution of specific native sites could give an in-depth way to understand the structure/composition-correlated properties and provide an efficient way to diversify and tailor the physicochemical properties of metal NCs ( Hirai et al, 2020 ; Kang et al, 2020 ). Several strategies have been developed to the synthesis of bimetallic Ag-Au NCs, such as one-pot co-reduction method ( Negishi et al, 2010 ; Kumara and Dass, 2011 ; Kumara and Dass, 2012 ) (spontaneous reduction of as-mixed Ag and Au precursors through balancing the redox potentials of metal pairs by thiol ligand ( Dou et al, 2014a ; Yu et al, 2016 )), classical galvanic replacement reaction approach ( Udayabhaskararao et al, 2012 ) (involves the spontaneous reduction of a noble-metal cationic by a less noble metal in solution driven by the difference in redox potentials), abnormal anti-galvanic replacement reaction approach ( Choi et al, 2010 ; Wu, 2012 ) (inverse process for galvanic replacement reaction recently observed for the synthesis of thiolate-protected Ag-Au NCs), and addition reaction ( Gan et al, 2018 ; Takano et al, 2018 ; Hirai et al, 2019 ) (a hydride-mediated controlled growth process).…”
Section: Introductionmentioning
confidence: 99%
“…Superatomic coinage bimetallic nanoclusters (NCs) with atomic precision are currently being extensively investigated due to their tunable structure, 1, 2 enhanced stability, [3][4][5] and significantly modified physicochemical properties, [6][7][8] as compared with homonuclear parent clusters. [9][10][11][12][13] Among these monolayerprotected clusters, the most studied combination is Au-Ag, as they are fully miscible in bulk. 14,15 It is well known that, a plethora of stable Au NCs have been synthesized and characterized in the past decades, 16,17 yet stable Ag NCs comprise a rather recent entry in the coinage metal NCs field.…”
Section: Introductionmentioning
confidence: 99%